Towards two decades of journalistic translation research (2000-2019): a corpus-based bibliometric study of the Translation Studies Bibliography - Ping, Yuan (Meta, 2021)
This paper provides a bibliometric analysis of journalistic translation research (JTR) from the past two decades. It is based on a corpus of 396 entries on journalistic translation and interpreting from the Translation Studies Bibliography (TSB) between 2000 and 2019. This study first consists of a bibliometric analysis of these entries from the aspects of author/editor, year, language, type, journal and publisher. It then explores prominent research topics and areas of focus based both on keywords provided by annotated entries in the TSB and on keywords and high-frequency nouns extracted from the abstracts as a result of corpus analysis. The study elaborates on various methodological approaches to studying journalistic translation according to the keywords provided in the entries of the TSB. The study found that: (1) most of the JTR was published by prestigious journals and publishers in English around 2010; (2) multimedia news about socio-cultural issues, published on various platforms, attracted the most attention from scholars; and (3) socio-cultural approaches have been the most prominent type of approach to journalistic translation over the past two decades. JTR research trends are also predicated according to the current development of the field.